Kajian Muatan Undang-Undang Pers Dan Undang-Undang Informasi dan Transaksi Elektronik Pada Aspek Kebebasan Berpendapat Bagi Jurnalis: (Studi Muatan Pasal 15 ayat (2) huruf d UU Pers dan Pasal 27 ayat (3) UU ITE 2008 Serta UU ITE 2016) - Diniroja, Syahda Aneira; Kartika, Adhitya Widya (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Journalistic activities now largely take place through digital media, giving rise to a dilemma between the application of the Press Law or the 2008 ITE Law and the 2016 ITE Law. In fact, the 2021 Joint Ministerial Decree on the ITE Law has confirmed that the Press Law is lex specialis. This study aims to examine the scope of the Press Law and the ITE Law in facing the development of digital media, as well as to analyse the construction and harmonisation of the law to maintain press freedom. The study uses a normative juridical method with a legislative and conceptual approach. The results show that the two regulations are not yet fully able to keep up with changes in the digital media landscape. There is a conflict of norms between Article 15 paragraph (2) letter d of the Press Law and Article 27 paragraph (3) of the ITE Law, thus requiring legal harmonisation. Harmonisation can be carried out without amending the Press Law, but by revising the ITE Law to add an exception clause for press products published digitally.